Here's the question you clicked on:
scottie21
Give the values of a, b, and c from the general form of the equation (2x + 1)(x - 2) = 0.
you can foil the problem by multiplying everything in
the first parenthesis by everything in the second
ok thanks can you help me with this one now
The line of symmetry of the parabola whose equation is y = ax2 - 4x + 3 is x = -2. What is the value of "a"?
im not sure, but i think you are supposed to substitute -2 in for x y = ax2 - 4x + 3 y= a(-2)^2-4x+3 y= 4a-4(-2)+3 y= 4a+8+3 y= 4a+11 -11 -11 _______________________________ y/4-11/4=4a/4 11-y/4 = a Im not sure! though